Mencium tangan, membungkukkan badan: Etos budaya Sunda, Yogyakarta, Madura - Metta Rachmadiana (HUMANITAS: Indonesian Psychological Journal, 2004)
The purpose of this kualitatif research is a deskriptif overview of a social reality and cultural fenomena between Sundanese, Yogyakarta and Maduranese of a hand kiss and by bowing the body in show of honour and respect to others. 7 individuals were involved in this research representing each cultural backgrounds.Collective data and information was composed under an un-structured interview and an observation within three stages of research. The results of this research noted that the cultural fenomena of a hand kiss and bowing of the body occurred both in Yogyakarta dan Sunda. As in Madura itself the hand kiss is often sighted but the bowing of the body is fading within generation.